2013
DOI: 10.4284/0038-4038-2013.145
|View full text |Cite
|
Sign up to set email alerts
|

The National Football League Season Wins Total Betting Market: The Impact of Heuristics on Behavior

Abstract: Sports and racetrack betting markets have been investigated by researchers for more than 50 years. Many authors have argued that the observed biases and inefficiencies in these markets are a consequence of bettors incorrectly assessing the objective probabilities that favorites or underdogs will win. This article is the first examination of the National Football League season wins total over/under betting market where the designations of favorite and longshot do not apply. The market is found to be highly inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, Tassoni (1996) shows data from betting on American football between 1976 and 1979 that the heuristic of representativeness almost does not appear. On the contrary, Woodland and Woodland (2015) detect the presence of the heuristic on later data from the years 1998 to 2010, at least in a weak form.…”
Section: Historically Dominant Teamsmentioning
confidence: 71%
“…However, Tassoni (1996) shows data from betting on American football between 1976 and 1979 that the heuristic of representativeness almost does not appear. On the contrary, Woodland and Woodland (2015) detect the presence of the heuristic on later data from the years 1998 to 2010, at least in a weak form.…”
Section: Historically Dominant Teamsmentioning
confidence: 71%
“…Furthermore, Vergin and Sosik (1999) found in a subset of NFL games that included Monday Night Football and playoff games that betting on the home team was a profitable betting strategy. Recent research by Fodor, DiFilippo, Krieger, and Davis (2013) and Woodland and Woodland (2015b) found performance of NFL teams in the prior season affects the betting strategies in the current season, while Woodland and Woodland (2015a) found the same heuristics in the NBA season wins total betting market. In European football, Kuypers (2000) found that bookmakers offered lower odds against the team that was considered the favorite in the match in order to take advantage of biased bettors who miscalculated the strength of the favorite.…”
Section: Sentiment In the Sports Betting Literaturementioning
confidence: 95%
“…Further evidence of this was later found in NFL (Badarinathi and Kochman 1994;Tassoni 1996;Vergin 2001). Woodland and Woodland found that gamblers tended to overreact to the performance of a team in the previous season in NBA (Woodland and Woodland 2015a), NFL (Woodland and Woodland 2015b) and Major League Baseball (Woodland and Woodland 2016). Despite the wealth of evidence for overreaction in betting odds for American sports, few studies appear to have investigated this effect in soccer.…”
Section: Biases In Sports Bettingmentioning
confidence: 99%